Global threat assessment 2009 - Gunaratna, Rohan (UNISCI Discussion Papers, 2009)
The year 2009 will bring an increase of national security threats: terrorism, emulation of Al-Qaeda, instability in Iraq as Coalition troops withdraw, persistent threat in Afghanistan and Pakistan and a spread of terrorism both in the global South and in the Western countries due to the radicalization of its Muslim diasporas do not bode well for the next year. If from a tactical point of view the intervention in Afghanistan may have weakened terrorism, it is definitely boosting it in the strategic level, in particular after the invasion of Irak, as the appeal for Yihad increases. The effect of Islamist “guerrillas” coming back home from the Iraqi and Afghan fronts can be devastating. Although the US are more protected than before the 11-S, its vulnerable allies (specially in the global South as the Levant, the East/Horn of Africa and South Asia) will further suffer the threat of terrorist groups adopting Al-Qaeda’s tactics as the latter turns into a training and coordinating hub protected in its stronghold in the Federally Administered Tribal Area (FATA) in Pakistan. But the solution goes beyond fighting terrorism, it entails fighting extremism and the Muslim perceptions of the West as a promoter of anti-Muslim policies. Solving the quagmire of Iraq, but also the plight of the Palestinian people and other local conflicts such as Kashmir or Mindanao becomes essential and will be the big challenge for the incoming Obama administration.